Preclinical Models of Atopic Dermatitis Suitable for Mechanistic and Therapeutic Investigations - Maskey AR; Mo X; Li XM (Dove Medical Press, 2024)
Anish R Maskey,1 Xian Mo,1,2 Xiu-Min Li1,3,4 1Department of Pathology, Microbiology and Immunology, New York Medical College, Valhalla, NY, 10595, USA; 2The Department of Allergy and Clinical Immunology, Guangzhou Institute of Respiratory Health, Guangzhou, People's Republic of China; 3Department of Otolaryngology, New York Medical College, Valhalla, NY, 10595, USA; 4Department of Dermatology, New York Medical College, Valhalla, NY, 10595, USACorrespondence: Xiu-Min Li, Department of Pathology, Microbiology, & Immunology, New York Medical College, Valhalla, New York, 10595, USA, Tel +1-914-595-1497, Email XiuMin_Li@nymc.eduAbstract: Atopic dermatitis (AD) is a complex immune-mediated abnormality of the skin characterized by impaired barrier function, eczematous dermatitis, chronic pruritus and itch. The immunological response in AD is mediated by a Th2-dominated immune response in the early acute phase followed by a Th1/ Th2 mixed immune response in the chronic phase. AD is the first step of the "atopic march" that progresses into food allergy, allergic rhinitis, and asthma. Different models are indispensable for studying AD pathogenesis and for designing pre-clinical studies for therapeutic discovery. They reflect the characteristic morphological features of typical human AD with regard to epidermal thickening, hyperkeratosis, acanthosis, and spongiosis and help understand the immunopathogenesis of the disease with respect to IgE levels and cellular infiltration of eosinophils, mast cells, and lymphocytes. Although it is difficult to replicate all human AD clinical features in a model, several AD in vivo models comprising spontaneous, induced, transgenic, and humanized and in vitro models, including 2D, co-culture, and 3D, have been described previously. However, several questions remain regarding whether these models satisfactorily reflect the complexity of human AD. Therefore, this review comprehensively highlights the diversity of currently available models and provides insights into the selection of suitable models based on research questions. It also summarizes the diverse mechanisms associated with each model, which may be valuable for better study design to test new therapeutic options.Keywords: atopic dermatitis, eczema, in vitro models, in vivo models, Th2 cytokine, microbiome